Shaykh Awelenji’s contribution to the liberation and globalization of arabic intellectualism in yoruba land (2018)
This paper examines the role of Shaykh Awelenje’s globalization of Arabic learning in the liberation process for Afro-Arabic learners in general and Yoruba in particular, using the internal and external experiences of this great scholar of the nineteenth century Nigeria as a case study. A distinct contribution of the paper to the current Arabic literature is many folds: 1) it conceptualizes Arabic learner’s liberation at the global level as a process driven by and contingent upon globalization of Arabic learning whose success is hinged on Arabic intellectual and scholarly legitimation and justification; and 2) it recognizes and demonstrates the liberating potential of globalization and identifies the challenges and limitations of these liberating forces in any attempt to liberate Arabic scholars globally. Drawing on both the case study and the literature on globalization and globalization of Arabic learning the paper concludes that: 1) globalization, driven by al-ilm dalatu-1- Mumin,ayna ma wajadahu akhadhahu, has created favorable conditions and opportunities for a global expansion of Arabic learning, aimed at learner’s liberation globally; 3) to achieve meaningful and realistic liberation of Arabic learners at the global level, liberation must be conceptualized as a long process that involves mutual understanding, education and ultimately, an intellectual revolution based on communicative events, triggered by literary scholarship of the type demonstrated in the life and works of Awlenje and 4) this process must identify and address specific differences among Arabic learners which stem, primarily, from culture, social class, ethnicity, race, nationality, religion, customs, tribal origin, social and political systems and the status of different nations within the so-called global intellectual society, as well as these nations status within the global, religion and political class systems.